Creating an efficient financial system : challenges in a global economy - Beck, Thorsten, 1967- 1967- (Policy research working paper, 2006)
"Financial sector development fosters economic growth and reduces poverty by widening and broadening access to finance and allocating society's savings more efficiently. The author first discusses three pillars on which sound and efficient financial systems are built: macroeconomic stability and effective and reliable contractual and informational frameworks. He then describes three different approaches to government involvement in the financial sector: the laissez-faire view, the market-failure view and the market-enabling view. Finally, the author analyzes the sequencing of financial sector reforms and discusses the benefits and challenges that emerging markets face when opening their financial systems to international capital markets. "--World Bank web site